Analisis Perbandingan Kinerja Keuangan Bank Umum Syariah Hasil Spin Off Dan Non Spin Off Periode 2013-2015 - Saraya Izazi Syarafina Hisyam; Dina Fitrisia Septiarini (Universitas Airlangga, 2016)
The aim of the study was to determine the difference in financial performance of Islamic banks results of acquisition and spin-offs around period year of 2013-2015. Financial performance measurement of Islamic banks used capital, asset quality, earning, and liquidity factor. Thus, study used quantitative research. The Islamic bank that are used as a sample in this study including one Islamic bank result of spin off and six Islamic bank result of acquisition. The financial performances analyzed using independent sample t-test and Mann-Whitney test. The variables used in financial performance assessment are CAR, NPF, ROA, BOPO and FDR. The data used for this study are secondary data gathered from per semester financial report in period of June 30th 2013 to June 30th 2015. The comparative analysis result in ratio of CAR, NPF, ROA, BOPO and FDR showed no differences in financial performance of Islamic banks result of acquisition and spin-off.